The Performance of the Tertiary Senior Students in Mathematics - Hyacinth Tolorio Gallarde (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Background: Mathematics is vital in the modern education of students nowadays. Objectives: the study was conducted to determine the students’ performance level in their Mathematics Foundation Courses, Mathematics Major Courses and Practice teaching and to find out if there exist a relationship between the performance outcomes. Methods: The quantitative descriptive-correlational method was used in the study where documentary analysis was more appropriate in gathering data which was taken from the grade sheets of the final grades of the students. The population of the study involved 51 fourth year students who were taking BSED major in Mathematics in the academic year 2016-2017. Results: The study revealed the students’ performance on their Mathematics foundation and Major Courses was on the very good level; and Practice teaching was on the superior level. It also revealed that there was significantly moderate correlation between Mathematics Foundation Courses and Mathematics Major Courses; and Mathematics Major Courses and Practice teaching while Mathematics Foundation Courses and Practice teaching were not significantly correlated. It is reccommended for improvement or re-visit in re-designing or updating the instructional course guide on Statistics II and Integral Calculus for the students to have much higher level of learning that would resulted in an excellent level of performance. Keywords: Performance, Tertiary Senior Students, Mathematics